Metafora Waktu dan Penalaran Temporal dalam Perspektif Budaya Waktu - Dyah Triarini Indirasari; Harry Susianto; Guritnaningsih Guritnaningsih (Faculty of Psychology Universitas Gadjah Mada, 2019)
Time is an abstract concept that can be understood by making an analogy or a metaphor from a more concrete concept such as a spatial construct. Previous studies found that people from different cultures and languages constructed time movement differently. In addition, the use of specific time metaphor tends to activate different type of temporal reasoning. Time metaphor studies related to Indonesian’s culture and language are still limited. Although it is known that Indonesians tend to use different temporal reasoning compare to other countries, how their time metaphors may have impact on their temporal reasoning is still unknown. It is then important to further investigate the effect of time metaphor on time reasoning particularly in different cultural contexts and how it may have impact on people behavior. This paper will discuss some findings in the topic of time metaphor and temporal reasoning, including the influence of culture on time conception.